Analysis of Material Thickness Effect on Die Clearance in Deep Drawing Process of Inner Body Components - Komarudin; Jacky Mianda Siagian; Taufik Nur Isman; Denny Prumanto; Bintang Ady Pradana (Greenation International Journal of Engineering Science, 2026)
This study investigates the effect of material thickness on die clearance in the deep drawing process of automotive inner body components. In sheet metal forming, improper parameter selection frequently leads to defects such as wrinkling, burr formation, and fracture, which reduce product quality and production efficiency. Despite extensive studies on stamping processes, the interaction between material thickness and optimal die clearance remains a critical issue in industrial applications. An experimental approach was conducted using a material thickness of 0.8 mm under controlled process conditions. Key parameters, including cutting force, stripping force, drawing force, springback, and material elongation, were measured and analyzed. The results indicate that the optimal die clearance lies within the range of −0.06 mm to +0.11 mm. At this condition, the cutting force reached 39,424 Kgf, while stripping and drawing forces were recorded at 1,971.2 Kgf and 5,708.8 Kgf/mm², respectively. The springback value was measured at 1.8 N/mm², and material elongation reached 3.67 mm. The findings demonstrate that die clearance must be carefully adjusted according to material thickness to ensure stable material flow and minimize defect formation. The novelty of this study lies in the experimental determination of a practical clearance range under actual production conditions. This research provides valuable insights for optimizing die design and improving manufacturing performance.